EFFECTS OF CRUDE OIL POLLUTED SOIL ON THE SEEDLING GROWTH OF PENNISETUM GLAUCUM (L.) R. BR. - Muhammad SHAFIQ (Journal of Plant Development, 2017)
Pollution by crude oil is an important environmental issue all around the world. Increase in oil pollution level in the environment produce toxic effects on flora and fauna of the region. The effects of different levels (0%, 5%, 10%, 15%, and 20%) of crude oil polluted soil on the growth of pearl millet (Pennisetum glaucum) were studied. The polluted soil affected the root, shoot length, seedling size, number of leaves and leaf area of P. glaucum. The significant (p<0.05) effects of polluted soil on fresh and dry weight of root, stem, leaves, and seedling of P. glaucum were also recorded. Leaf area, leaf number and total seedling dry weight were noticeably reduced in 10 and 15% polluted soil than control soil treatment. Principally, 20% crude oil polluted soil treatment exhibited highest percentage of decrease in most of the seedling growth parameters of P. glaucum than control. Hence, the effects on seedling growth parameters were increased with increasing levels of polluted soil. For most of the growth parameters, the mean values obtained were found higher for the control soil and progressively decreased from 5-20% crude oil polluted soils. The seedlings of P. glaucum were also tested for tolerance to polluted soil treatment. The results showed that the seedlings of P. glaucum showed high percentage of tolerance to low concentration (5%) of polluted soil treatment as compared to control soil treatment (0%).